Antibody-free isolation and regulation of adherent cancer cells via hybrid branched microtube-sandwiched hydrodynamic system. Issue 8 (18th February 2020) - Feng, Jianming; Mo, Jingshan; Zhang, Aihua; Liu, Di; Zhou, Lingfei; Hang, Tian; Yang, Cheng; Wu, Qianni; Xia, Dehua; Wen, Rui; Yang, Jiang; Feng, Yuping; et al.
Abstract : A facile methodology for multifunctional antibody-free isolation and in situ delivery of tumor cells based on hybrid branched microtube-sandwiched hydrodynamic system. Abstract : The detection of circulating tumor cells (CTCs) has achieved promising progress for early diagnosis and disease analysis. Microfluidic chip techniques have recently promoted the technologies of CTC sorting and analysis, yet seldom can the microfluidic chips for CTC enrichment via antibody-free capture provide in situ regulation of both extracellular and intracellular activity, which would be advantageous for cell-based pharmaceutical therapeutics and screening. Herein, we have demonstrated a hybrid TiO2 /ZnO branched microtube array (HBMTA)–sandwiched hydrodynamic device that integrates the multiple functions of selective enrichment of adherent tumor cells in an antibody-free manner and in situ delivery to the extracellular and intracellular spaces of the enriched tumor cells. More than 90% cancer cells were enriched on the device due to their preferential adhesion with the nano-branches of HBMTA, while more than 91% blood cells were eliminated from the device by constant hydrodynamic fluid shearing. For in situ regulation, temporally and spatially controlled extracellular delivery to the enriched tumor cells could be precisely achieved through the hollow structures of the HBMTA. In addition, reagents ( e.g. propidium iodide) could be delivered into the intracellular spaces of enriched tumor cells by coupling an electric field to nondestructively perforate the cell membrane. Our study not only offers a promising and facile strategy for antibody-free isolation of tumor cells, but also provides unique opportunities to facilitate cancer research, including antitumor drug screening and personalized therapeutics.